High expression of TRF2, SOX10, and CD10 in circulating tumor microemboli detected in metastatic melanoma patients. A potential impact for the assessment of disease aggressiveness. (6th March 2016) - Long, Elodie; Ilie, Marius; Bence, Coraline; Butori, Catherine; Selva, Eric; Lalvée, Salomé; Bonnetaud, Christelle; Poissonnet, Gilles; Lacour, Jean‐Philippe; Bahadoran, Philippe; Brest, Patrick; Gilson, Eric; et al.
Abstract: Circulating tumors cells (CTCs) can be detected in the blood of metastatic melanoma patients (MMPs) both as isolated circulating tumor cells (iCTCs) and circulating tumor microemboli (CTMs), but their clinical significance remains unknown. The aim of this work was to evaluate the prognostic impact in metastatic cutaneous melanoma of CTMs and iCTCs identified by a cytomorphological approach using the isolation by size of tumor cell (ISET) method. We characterized the phenotype of CTCs using anti‐PS100, anti‐SOX10, anti‐CD10, and anti‐TRF2 antibodies. 128 MMPs and 37 control healthy individuals with benign nevi were included in this study. Results were compared to the follow‐up of patients. 109/128 (85%) MMPs showed CTCs, 44/128 (34%) with 2 to 6 CTMs and 65/128 (51%) with 4 to 9 iCTCs. PS100 expression was homogeneous in iCTCs and heterogeneous in CTMs. SOX10, CD10, and TRF2 were mainly expressed in CTMs. None of the control subjects demonstrated circulating malignant tumor cells. Overall survival was significantly decreased in patients with CTMs, independently of the therapeutic strategies. In conclusion, the presence of CTMs is an independent predictor of shorter survival from the time of diagnosis of MMPs. Abstract : We show that circulating tumor cells are frequently detected in blood of MMPs either isolated or as circulating tumor microemboli. The detection of circulating tumor microemboli (CTMs) is synonymous of a higher metastatic potential at baseline and after first line of treatment with Vemurafenib. Higher expression of TRF2, CD10, and SOX10 in CTMs correlated with worse prognosis in MMPs, whereas these molecules were only weakly or not expressed in isolated circulating tumor cells (CTCs).